Trial of DC Submersible Pump 12 Volt 50 Watt with Solar Power and Relationship between Water Discharge and Storage Height - Ahmad Swandi; Sri Rahmadhanningsih; Sparisoma Viridi; Inge Magdalena Sutjahja (Universitas Negeri Malang, 2021)
One of the biggest problems for farmers in the dry season is the lack of water supply for irrigation. Currently, various types of pumps have been widely used, such as fuel pumps and pumps with PLN electricity. However, the costs required to operate these tools are pretty expensive. The solution to overcome this is using DC submersible pumps using solar panels as an energy source. The purposes of this study are to (1) determine the duration of operation of the DC submersible pump with the specifications of the battery and solar panels used, and (2) determine the productivity of the DC submersible pump in terms of the resulting discharge for various storage height conditions used. The research method used is an experimental research method using a quantitative approach. The results of this study are (1) DC submersible pump can operate for 240 minutes with 20 Ah battery at maximum voltage and uses 60 Wp solar panels, and (2) the height of the storage has an effect on the resulting discharge, there is a reduction in the resulting discharge every 0.5 meters increase in the height of the storage. Based on the analysis results, the maximum height limit for submersible pump push is 3.7 meters using a 3 per 4 inch hose. The results of this study can be a reference for farmers or users to determine the height of the water storage.DOI: 10.17977/um024v6i22021p061